Faktor-Faktor yang Mempengaruhi Penggunaan Informasi Akuntansi pada UMKM di Kecamatan Kibin - Indyyati Indyyati; Heni Indah Pratiwi; Lia Uzliawati (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
Abstract: The Purpose Of This Reseach Is To Find Out There are still many Micro, Small and Medium Enterprises in the Kibin District that have not applied the principles of accounting information; Micro, Small and Medium Enterprises in the Kibin District have not received empowerment and education regarding accounting information to be applied in their business activities from the Kibin District Government authorities; and Micro, Small and Medium Enterprises in the Kibin District area only rely on simple financial records so that it is difficult to access capital services for banking companies. The purpose of this study was to determine the effect of business scale, education and training simultaneously on the use of accounting information for MSME actors in Kibin District. The research method used is causal associative with a quantitative approach. The results showed that partially the business scale variable (????1) had a positive influence on the variable use of accounting information (Y), then the education variable (????2) had an influence on the variable use of accounting information (Y). then the training variable (????3) has a negative effect on the variable use of accounting information (Y). Meanwhile, it simultaneously shows that there is an influence between the variables of business scale, education and training simultaneously (business scale, education and training) on the variable of using accounting information (Y) in Kibin District.